The drama-free workplace how you can prevent unconscious bias, sexual harassment, ethics lapses, and inspire a healthy culture - Perez, Patti, 1967 - author (Hoboken, New Jersey John Wiley & Sons, Inc., 2019)
"The Drama-Free Workplace is a hands-on guide filled with proven strategies and guidance for creating and sustaining a cohesive, collaborative workplace culture that enables widespread innovation, increases productivity, and greater revenue."
Prof. Sia (Recommending faculty) - Bookfair 2019
Keywords: Personnel management; Employee morale; Problem employees; Organizational behavior; Corporate culture